2012
DOI: 10.1889/jsid20.6.318
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the grain size on hysteresis of liquid‐crystalline Blue Phase I

Abstract: Abstract— Three different blue‐phase I liquid‐crystal samples with different grain‐size distribution were studied. Polycrystalline platelet grains reflects light in the visible region and have been observed under a polarizing optical microscope. Green and blue grain areas have been measured and then the statistical histogram by the Gaussian distribution function was fitted and the mean grain size was calculated. The effect of hysteresis on grain size has been compared for the three samples. Hysteresis depends … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Therefore, increasing this threshold value V t beyond the maximum voltage V m is a reasonable strategy to reduce Δ V . Successes in reducing Δ V were also reported for particular compositions—including nanoparticle composites—appropriate choice of the curing temperature, or preparation of large BP monodomains …”
Section: Kerr Effect In Polymer‐stabilized Blue Phases: Recent Develomentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, increasing this threshold value V t beyond the maximum voltage V m is a reasonable strategy to reduce Δ V . Successes in reducing Δ V were also reported for particular compositions—including nanoparticle composites—appropriate choice of the curing temperature, or preparation of large BP monodomains …”
Section: Kerr Effect In Polymer‐stabilized Blue Phases: Recent Develomentioning
confidence: 96%
“…Concerning the field‐induced birefringence, early studies have revealed a field‐induced biaxiality . In addition, some recent studies indicate that a uniform BP alignment can enhance the electro‐optic performance . This finding abates the hope that PSBP can be applied without using any alignment layer.…”
Section: Further Subjects Of Recent Studiesmentioning
confidence: 98%
“…The results show that the hysteresis (ΔV50) of the first order diffraction efficiency is ~10 V for 1-D and 2-D BPLC gratings, which corresponds to ~6.67% of the voltage of maximum diffraction efficiency (Vmax ~ 150 V). The small hysteresis observed is due to the large domain size (over 50 μm) of the BPLC sample [31], and the operating temperature of the BPLC grating is close to the temperature of phase transition between BPI and blue phase II (BPII) (~45.5 °C) [30]. However, a method can be utilized to reduce the hysteresis, such as using the BPLC sample with a temperature in the BPII range [30], polymer stabilized blue phase liquid crystal (PSBPLC) [32][33][34], and elliptical protrusion electrodes [35].…”
Section: Resultsmentioning
confidence: 94%
“…Hysteresis can be seen as an outcome of an electrically disturbed BPs. Several reports have confirmed that both orientating and growing large platelets have positive impacts on the elimination of hysteresis [80,128].…”
Section: Optical Isotropy and Fast Electro-optic Responsementioning
confidence: 89%